Breaking Bad in Business Education: Impacts on Student Incivility and Academic Dishonesty. (September 2017) - Offstein, Evan H.; Chory, Rebecca M.
The present study examines instructors' attempts to increase student satisfaction through what we predict to be destructive communication tactics. Results indicate that business majors reported being more likely to engage in incivility and academic dishonesty in courses taught by professors who attempted to gain student favor through gossiping, self-disclosure, and downward convergence. Furthermore, perceptions of the instructor's ethical character mediated the relationships between instructor behaviors and student incivility. Given the centrality of the professor in developing future managers and employees, we discuss implications for business and professional education and advocate for a return to a more traditional business professor role.